P‐29: Mitigating Color Deficiency in Graphical Display. Issue 1 (30th May 2018) - Ward, Greg; Nazari, Mina Rafi; Soudi, Afsoon; Akhavan, Tara; Yoo, Hyunjin; Gerhardt, Jeremie; Clark, James J.
Abstract : We propose a technique for adjusting displays to compensate for deficiencies in viewers' color perception. The method proposed finds graphical elements of the image and recolors them using a color palette designed specifically for colorblind viewers. We present results of user studies demonstrating the advantages of this approach.